Implementation of the Waterfall Method in Mobile Web-Based Outpatient Online Registration Information System - Rahmadoni, Jefril; Akbar, Ricky; Indrapriyatna, Ahmad Syafruddin; Cantika, Annisa Hasifah (Departemen Sistem Informasi, Fakultas Teknologi Informasi, Universitas Andalas, 2024)
The goal of this study is to create, design, and implement a web-based outpatient registration application at Batusangkar Regional Hospital. The research method used is qualitative descriptive research, which involves a series of activities or processes that reveal system processes. This study's system development employs the waterfall method, as well as data collection techniques such as data documentation, interviews, and observation. This registration application was designed using the UML (Unified Modeling Language) model, which includes use case diagrams, activity diagrams, sequence diagrams, and class diagrams. Designing database logic with MySQL. The system was designed and implemented using XAMPP as a web server, PHP MySQL as a database, Visual Studio as a web design editor, and Android Studio as an Android design editor. It is hoped that this application will allow patients to easily register from anywhere and access the most up-to-date information and practice schedules for polyclinic doctors at Batusangkar Regional Hospital.